From Karl Wurm and Guy Scadding's staging to 18F-FDG PET/CT scan phenotyping and far beyond: perspective in the evading history of phenotyping in sarcoidosis - Papiris, Spyros A.; Kolilekas, Lykourgos; Rivera, Natalia; Spanos, Michail; Li, Guoping; Gokulnath, Priyanka; Chatterjee, Emeli; Georgakopoulos, Alexandros; Kallieri, Maria; Papaioannou, Andriana I.; Raptakis, Thomas; Apollonatou, Vasiliki; et al. (Frontiers in Medicine, 2023)
Sarcoidosis is an inflammatory granulomatous disease of unknown etiology involving any organ or tissue with any combination of active sites, mostly silent clinically. This unpredictability dictates the highly variable natural history of the disease and the necessity to cluster cases at diagnosis based on clinical and/or imaging common characteristics in the attempt to divide patients to more homogeneous phenotypes possibly with similar clinical behavior, prognosis, outcome and therefore therapeutic requirements. In the course of disease’s history this attempt relates to the availability of means of detection of sites involved, from the Wurm and Scadding’s chest x-ray staging through the ACCESS and the WASOG Sarcoidosis organ assessment instruments, the GenPhenReSa study to the 18F-FDG PET/CT scan phenotyping and far beyond to new technologies and/or the current “omics”. The hybrid molecular imaging of the 18F-FDG PET/CT scan by unveiling glucose metabolism of inflammatory cells is able to identify with high sensitivity inflammatory active granulomas, the hallmark of sarcoidosis, even in sites clinically and physiologically silent and as recently shown succeeded to identify an unexpected ordered stratification into four phenotypes: I) hilar-mediastinal nodal, II) lungs and hilar-mediastinal nodal, III) an extended nodal supraclavicular, thoracic, abdominal, inguinal and IV) all the above plus systemic organs and tissues, appearing therefore the ideal phenotyping instrument. At the “omics era”, studies could provide significant, distinct and exclusive insights into sarcoidosis phenotypes linking clinical, laboratory, imaging and histologic characteristics with molecular signatures. In this context the personalization of treatment for sarcoidosis patients might have reached its real aim.